Análise de custo-efetividade dos procedimentos de radioterapia de intensidade modulada e de conformação tridimensional utilizados no tratamento do câncer de próstata localizado - Arruda, Caio Viani (2021)
The National Cancer Institute (INCA) estimates that 65,840 new cases of prostate cancer will be diagnosed in 2020, thus being the most frequent solid tumor in Brazilian men, with peak incidence at 62 years of age. Currently, most cases of prostate cancer are diagnosed at an early stage. In this scenario several studies point out that there are several treatment options, among the various options it is worth highlighting the radiotherapy, there are several treatment techniques, such as beam intensity modulated radiotherapy (IMRT), and 3D conformational radiotherapy, the most used in daily clinical practice. Currently in Brazil, the unique health system provides remuneration of radiotherapy services only for the treatment of prostate cancer using the RT 3D technique. However, recent evidence has pointed out the IMRT as more effective with respect to late toxicity, with no difference in mortality when compared to the RT3D, and there are doubts about its advantage in terms of cost effectiveness. Thus, the objective of this study is to address this gap by developing a decision analysis model that integrates currently available published evidence on the incidence of long-term post-treatment toxicity to compare the incremental cost-effectiveness between IMRT and RT3D for the treatment of localized prostate cancer.